Factors Associated with Dietary Non-Adherence among Chronic Kidney Disease Patients Undergoing Hemodialysis at RSU Imelda Pekerja Indonesia, Medan - Ali Asman Harahap; Syahrul Handoko Nainggolan; Candra Meriani Damanik; Yuni Shanti Ritonga; Satriani H. Gultom; Lamtiur Purba (International Journal of Public Health, 2025)
Background: Dietary adherence is a crucial component in the management of patients with chronic kidney disease (CKD) undergoing hemodialysis. Non-adherence may lead to metabolic imbalance, increased morbidity, and reduced quality of life.Objective: To identify factors associated with dietary non-adherence among patients with CKD undergoing hemodialysis at Imelda Hospital, Medan. Methods: A cross-sectional study was conducted among patients undergoing routine hemodialysis. Data were collected using structured questionnaires assessing knowledge, attitudes, and family support related to dietary adherence. Statistical analysis was performed using chi-square tests and logistic regression with a significance level of p < 0.05. Results: Knowledge, attitudes, and family support were significantly associated with dietary non-adherence (p < 0.05). Family support was identified as the most influential factor. Conclusion: Dietary non-adherence among hemodialysis patients is influenced by knowledge, attitudes, and family support. Strengthening patient education and family-centered nursing interventions is essential to improve dietary adherence.